Water, ice, and climate change in northwest Greenland. (18th March 2020) - Nuttall, Mark
Abstract: Along the coastal areas of northwest Greenland, sea ice is crucial to people's livelihoods. People in the region have long depended on hunting marine mammals such as seals; walrus; narwhal, beluga, fin, and minke whales; and polar bears, as well as fishing for fjord cod, Greenland halibut, salmon, and Arctic char. Terrestrial animals such as reindeer and Arctic foxes have also been of some importance, as have musk ox in some areas. However, the effects of a changing climate on the marine environment are stark, immediate, and tangible. Ice is melting, and coastal waters are warming. Sea ice, glaciers, coastlines, and seas have become sites and objects for new forms of environmental governance shaped by ideas of unique and fragile ecosystems under threat at a moment of planetary crisis. Conservation organizations frame the Arctic as a zone of climate change crisis and have launched campaigns—underpinned by narratives of ruination—to protect what are termed last areas of ice. However, Inuit organizations are also working to ensure that environmental governance and conservation policymaking do not exclude local communities in the region and are campaigning for protected marine areas in which wildlife management systems and community‐based monitoring take note of indigenous rights and incorporate indigenous knowledge. This article is categorized under: Science of Water > Water and Environmental Change Human Water > Rights to Water Human Water > Water Governance Water and Life > Conservation, Management, and Awareness Abstract : This is a hunting camp at the ice edge near Qeqertarsuaq, northwest Greenland. Hunters from Qaanaaq have traditionally spent time at the ice edge in spring, but in recent years, the ice has been thinner and slushier, and they talk of how the ice edge has become a place of greater instability, of constant shifts, and the movement and breaking apart of brittle floes, which makes camping and hunting there more difficult and dangerous. Photo: Mark Nuttall.